Arrestee Drug Abuse Monitoring Program II in the United States, 2010 - Hunt, Dana ([Verlag nicht ermittelbar], 2011)
The Arrestee Drug Abuse Monitoring (ADAM II) program was designed to monitor trends in drug use among arrested populations in key urban areas across the United States. The first ADAM data collection was instituted in 2000 as a replacement for the Drug Use Forecasting program (DUF), which employed a non-scientific sampling procedure to select primarily felony arrestees in 23 urban areas throughout the country. The year 2000 revision of ADAM instituted a representative sampling strategy among booked male arrestees in an expanded network of 35 sites. The program was suspended by the National Institute of Justice in 2003 and restarted in 2007 with funding from the Office of National Drug Control Policy (ONDCP). With ADAM II, ONDCP and its contractor, Abt Associates Inc., initiated a new data collection that replicated the ADAM methodology in order to obtain data comparable to previously established trends. ADAM II implemented two quarters of data collection in ten sentinel ADAM sites to revive monitoring drug trends, with a particular focus on obtaining valid and reliable information on methamphetamine use. Representing minimal adjustments to the previously employed ADAM survey, the ADAM II survey collected data about drug use, drug and alcohol dependency and treatment, and drug market participation among booked male arrestees within 48 hours of arrest. A total of 8,332 arrestees were interviewed during the second and third quarters of 2010. Collection occurred in two cycles in booking facilities at each site to provide estimates for two calendar quarters each year. Data in this file were collected beginning April 1, 2010, and ending September 30, 2010. Participation was voluntary and confidential, and the procedures included a personal interview (lasting approximately 20 minutes) and collection of a urine specimen. Demographic variables include age, race, most serious charge, date of arrest, time of arrest, and education level. The data also include whether the provided urine specimen was positive for several drugs including marijuana, cocaine, PCP, methamphetamines, and barbiturates.